E16 Diffusion Tensor Imaging And Neuropsychiatric Disturbance In Huntington 's Disease. (17th September 2014) - Gregory, S; Scahill, RI; Stopford, C; Orth, M; Durr, A; Leavitt, B; Roos, RAC; Langbehn, DR; Johnson, H; Rees, G; Tabrizi, SJ; Craufurd, D
Abstract : Background: Huntington's disease (HD) is commonly associated with psychiatric disturbance. Often evident in premanifest gene-carriers, little is understood about the neural bases underlying these HD symptoms. While structural imaging has so far failed to provide any major insight, Diffusion Tensor Imaging (DTI) can be used to investigate connectivity between brain regions and any putative microstructural changes that may occur in HD. Aims: To examine structural connectivity associated with depression, apathy and irritability in HD gene-carriers. Methods: DTI data was collected from 39 premanifest and 45 early-HD participants, as part of the TrackHD study and was analysed using whole-brain Tract-Based Spatial Statistics to extract fractional anisotropy (FA) values – a surrogate marker for tract integrity and efficacy of communication between brain regions. Regression analyses were performed on all gene-carriers using HADS depression and PBA apathy and irritability scores. Results: High disease load (measured by CPO) was associated with highly significant, whole-brain corrected correlations between depression scores and reduced FA in the bilateral splenium of the corpus callosum. There were significant widespread negative associations between irritability scores and FA. Interestingly, low disease load participants demonstrated significant correlations between irritability scores and FA reduction. There were no significant associations between apathy and FA. Conclusions: Both depression and irritability are associated with reductions in white matter integrity in HD. The opposite relationships between FA and measures of depression and irritability as a function of disease progression suggest that diverse mechanisms associated with both the onset and progression of psychiatric disturbance in HD.